Creative workers: Returns to education and experience. The evidence from Australia - Kamil Zawadzki; Monika Wojdyło (Economic and Environmental Studies (E&ES), 2018)
This paper uses unit record data from the Household, Income and Labour Dynamics in Australia (HILDA) Survey conducted on 7340 individuals. The mapping methodology of Australian creative economy was implemented to extract 455 workers belonging to 27 creative occupations. To compare differentiation of influence of human capital on the creative workers' hourly wage with the general population's returns to education and work experience, the quantile and ordinary least squares regressions were used. Results indicate larger wage gap among creative workers than among other working persons. Returns to education and to experience are similar for the creative workforce, while in the general population return to education is three times as large as to experience. The most important finding is that investing in school education is less profitable for creative economy workers than that for other working people. Besides, there is a considerable difference in the profitability of investment in human capital among creative men and women.
Keywords: J24; J31; O15; Z11; 330; human capital; creative workers earnings; returns to education; returns to experience